Persistent infection with Staphylococcus pseudintermedius in an adult oncology patient with transmission from a family dog. (2nd April 2020) - Blondeau, L.D.; Rubin, J.E.; Deneer, H.; Kanthan, R.; Morrison, B.; Sanche, S.; Rypien, C.; Dueck, D.; Beck, G.; Blondeau, J.M.
Abstract : Staphylococcus pseudintermedius is a well known commensal organism of dogs but also a canine opportunistic pathogen. Reports of this organism being recovered from specimens from humans might suggest an increase prevalence in human infections and/or improved diagnostic leading to more accurate identification. Here we report a case of persistent S. pseudintermedius infection in an adult female oncology patient including colonization of the tip of an indwelling catheter. Diligence by laboratories in correctly isolating and identifying this pathogen (including susceptibility testing) is essential for optimal patient care.